Detection and identification of phytoplasmas in peach based on woody indexing and molecular methods - Németh, M.; Ember, I.; Krizbai, L.; Kölber, M.; Hangyál, R.; Bozsics, J. (International Journal of Horticultural Science, 2001)
Symptoms resembling phytoplasma disease have been observed on peach trees in a seed-source plantation of stone fruits in south Hungary quite recently. In this publication we report on the results of woody indexing of symptomatic peach trees on GF 305 indicator in the field and under greenhouse conditions as well as on molecular studies. Phytoplasma infection detected on GF 305 indicators in greenhouse and field indexing was confirmed by PCR. Nested PCR was conducted using universal primer pairs followed by group and subgroup specific primers for the second amplification. RFLP analysis of nested PCR products was performed using Rsal restriction enzyme. Based on the results of molecular studies it can be concluded that phytoplasmas, belonging to the European stone fruit yellows subgroup (16SrX-B) were identified in peach trees. Further studies on symptomatic peach trees originating from different parts of Hungary are in progress.